Prognostic value of non-obstructive coronary artery disease based on coronary computed tomography angiography in a long-term follow-up and multicenter study - Zengfa Huang; Xiaowei Chen; Wanpeng Wang; Xinyu Du; Beibei Cao; Mei Li; Yang Yang; Xi Wang; Jiong Huang; Jinghang Zhu; Xu Zhao; Xiang Wang (Scientific Reports)
Abstract This study investigates the long-term prognostic significance of non-obstructive coronary artery disease (CAD) in predicting the risk of all-cause death in a multicenter study. Three hospitals in Wuhan participated in this retrospective, observational, multicenter study of 7320 patients with suspected of having CAD and who underwent clinical coronary computed tomography angiography (CTA) from June 2011 to December 2015. According to coronary CTA, the extent of CAD was categorized as non-obstructive, obstructive, and no CAD. The primary outcome was all-cause mortality. A total of 611 patients experienced all-cause mortality with a median duration of 8.0 years (7.2–8.9). The annualized mortality rate was 0.50 (95% CI: 0.43–0.58), 1.31 (95% CI: 1.16–1.47), and 2.18 (95% CI: 1.93–2.46) for the no CAD, non-obstructive CAD, and obstructive CAD, respectively. There was a significant association between the classification and the increased cumulative events, as shown by the Kaplan-Meier survival curve (P < 0.001). The multivariate Cox model showed that the hazard ratios (HR) for predicting all-cause mortality from 1.42 (95% CI: 1.15–1.75, P = 0.001) in non-obstructive CAD to 1.87 (95% CI: 1.50–2.33, P < 0.001) in obstructive CAD compared with no CAD. At 8-year follow-up, patients with non-obstructive CAD detected by coronary CTA had a 1.42-fold increased risk of all-cause mortality compared to patients without evidence of CAD. Thus, these findings suggest that non-obstructive CAD is clinically significant and that further investigation of interventions to improve the prognosis of these patients is warranted.